2004
DOI: 10.1111/j.1745-6592.2004.tb00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals and Other Organic Waste Water Contaminants Within a Leachate Plume Downgradient of a Municipal Landfill

Abstract: Ground water samples collected from the Norman Landfill research site in central Oklahoma were analyzed as part of the U.S. Geological Survey (USGS) Toxic Substances Hydrology Program's national reconnaissance of pharmaceuticals and other organic waste water contaminants (OWCs) in ground water. Five sites, four of which are located downgradient of the landfill, were sampled in 2000 and analyzed for 76 OWCs using four research methods developed by the USGS. OWCs were detected in water samples from all of the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(66 citation statements)
references
References 19 publications
3
61
1
1
Order By: Relevance
“…The presence of pharmaceuticals in groundwater beneath or downgradient of a landfill has been confirmed by several authors (Ahel and Jelicic, 2001;Ahel et al, 1998;Eckel et al, 1993;Holm et al, 1995). Two recent studies (Barnes et al, 2004;Buszka et al, 2009) investigating the occurrence of groundwater down gradient of landfills detected a range of industrial compounds (detergents, antioxidants, fire retardants, plasticisers) as well as PPCPs (antibiotics, anti-inflammatories, barbiturates) and the caffeine and the nicotine metabolite cotinine.…”
Section: Source Termsmentioning
confidence: 76%
“…The presence of pharmaceuticals in groundwater beneath or downgradient of a landfill has been confirmed by several authors (Ahel and Jelicic, 2001;Ahel et al, 1998;Eckel et al, 1993;Holm et al, 1995). Two recent studies (Barnes et al, 2004;Buszka et al, 2009) investigating the occurrence of groundwater down gradient of landfills detected a range of industrial compounds (detergents, antioxidants, fire retardants, plasticisers) as well as PPCPs (antibiotics, anti-inflammatories, barbiturates) and the caffeine and the nicotine metabolite cotinine.…”
Section: Source Termsmentioning
confidence: 76%
“…Their occurrence is most often a result of municipal wastewater discharge, as these compounds are not completely removed during treatment (4). Other sources of pharmaceuticals and EDCs in water include runoff from agricultural fields, concentrated animal feeding operations, landfill leachates, and urban runoff (5)(6)(7). Scientists and regulators are concerned about what level of risk may be associated with the presence of pharmaceuticals and EDCs in drinking water, as many drinking water treatment plants (DWTPs) use source water impacted by wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Slack (2007) reviewed the detections of xenobiotic compounds in leachate including halogenated and aromatic hydrocarbons, phenols (including bisphenol A), alkyl phenols (including nonyl phenol), pesticides, phthalates, pharmaceuticals, sulfonates, sulfones and sulfonamides (including n-butylbenzenesulfonamide (BBSA)), pyridines (including nicotine), carboxylic acids, alcohols, ethers and ketones, as well as caffeine, benzthiazoles and anilines. Barnes et al (2004) and Buszka et al (2009) found a range of microorganics in groundwater downgradient of landfills including detergents, antioxidants, fire retardants, plasticisers, antibiotics, ant-inflammatories, barbiturates, caffeine and cotinine. Zheng et al (2013) describe the use of organic water pollutant fingerprints to track the movement of industrial materials.…”
Section: Introductionmentioning
confidence: 99%